SCAMPER texnikasi asosida bola bilan ishlashning maxsus mashqlari va faoliyat turlarini tashkil etish usullari - Karimova, A. (SCIENCE and SOCIETY, 2025)
The article talks about teaching creative and critical thinking by applying the SCAMPER technique through special interesting exercises in the field of preschool education.